2018
DOI: 10.1002/lt.25005
|View full text |Cite|
|
Sign up to set email alerts
|

Normothermic machine perfusion of donor livers without the need for human blood products

Abstract: Normothermic machine perfusion (NMP) enables viability assessment of donor livers prior to transplantation. NMP is frequently performed by using human blood products including red blood cells (RBCs) and fresh frozen plasma (FFP). Our aim was to examine the efficacy of a novel machine perfusion solution based on polymerized bovine hemoglobin‐based oxygen carrier (HBOC)‐201. Twenty‐four livers declined for transplantation were transported by using static cold storage. Upon arrival, livers underwent NMP for 6 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
104
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(114 citation statements)
references
References 27 publications
9
104
1
Order By: Relevance
“…42 The preconditioning effects achieved through active replenishment of ATP stores may help renal grafts mitigate the injurious effects of reperfusion. 27 We recorded sustained ATP production in the HBOC group following the first hour of perfusion, which was associated with a consistent increase in renal energy charge throughout the perfusion. 44 Because of lower oxygen affinity and lessened viscosity of an HBOC-201 solution (Hemopure units are 1 × 10 −8 the size of an RBC) compared to a red cell-based solution, the former is able to deliver significantly higher oxygen levels, thereby achieving a superior cellular ATP content within perfused tissues.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…42 The preconditioning effects achieved through active replenishment of ATP stores may help renal grafts mitigate the injurious effects of reperfusion. 27 We recorded sustained ATP production in the HBOC group following the first hour of perfusion, which was associated with a consistent increase in renal energy charge throughout the perfusion. 44 Because of lower oxygen affinity and lessened viscosity of an HBOC-201 solution (Hemopure units are 1 × 10 −8 the size of an RBC) compared to a red cell-based solution, the former is able to deliver significantly higher oxygen levels, thereby achieving a superior cellular ATP content within perfused tissues.…”
Section: Discussionmentioning
confidence: 82%
“…[20][21][22][23] Organs undergoing ex vivo perfusion at normothermic temperatures require adequate oxygen delivery to meet metabolic demand. [26][27][28] The promise of these agents lies in their long shelf half-life, ease of use, easy accessibility, and negligible infectious risks. [26][27][28] The promise of these agents lies in their long shelf half-life, ease of use, easy accessibility, and negligible infectious risks.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In preclinical studies using human donor livers, it was previously shown that a short period of DHOPE prior to NMP results in increased ATP concentrations, less hepatobiliary injury and improved function during the NMP phase, compared to direct end-ischemic NMP. 14,16,17 Based on the presumed complementary effect of (D)HOPE and NMP we have combined these two techniques in a clinical machine perfusion protocol using an HBOC-201-based solution. A perfusion fluid based on human red blood cells (RBC) is frequently used for NMP.…”
Section: Introductionmentioning
confidence: 99%
“…For the application of this combined machine perfusion protocol we have developed a perfusion fluid that can be used at various temperatures and eliminates the use of a third party human blood product. 14 Our group reported higher ATP concentration, and cumulative bile production in discarded human livers undergoing NMP with an HBOC-201-based solution, compared to perfusion with an RBC-based perfusion fluid 16. Perfusion solutions based on RBC, which are mostly used for NMP, cannot be used at low temperatures due to increasing lipid membrane stiffness and the risk of hemolysis.…”
mentioning
confidence: 96%
See 1 more Smart Citation